An Investigation of the Associations Between Counterfactual Reasoning and Executive Functions in Chinese Preschool Children - Wu, Yanwen (Journal of cognition and development, 2025)
Counterfactual reasoning involves reasoning about what could have happened but did not happen in the past. It assists people to learn from experience to improve future performance. Different from English with subjunctive forms (e.g. if someone had done something), Chinese does not apply subjunctive forms. In Chinese, people often decide that a premise is counterfactual based on their knowledge of the past, which involves working memory. This study investigated counterfactual reasoning performance and the associations between counterfactual reasoning and executive functions in 257 Chinese 4- to 6-year-olds. Children completed counterfactual reasoning, working memory, inhibitory control, and receptive language tasks. Results showed that Chinese 4-year-olds achieved above-chance counterfactual reasoning performance. Also, working memory was significantly associated with counterfactual reasoning. Hence, Chinese children might solve counterfactual reasoning tasks without complex subjunctive forms relatively early, and working memory might assist counterfactual reasoning in Chinese.